Righting Software - Larus, Jim; Ball, Thomas, Manuvir Das; DeLIne, Robert; Fahndrich, Manuel; Pincus, Jon; Rajamani, Sriram; Venkatapathy, Ramanathan (IEEE Software, 2004)
What tools do we use to develop and debug software? Most of us rely on a full-screen editor to write code, a compiler to translate it, a source-level debugger to correct it, and a source-code control system to archive and share it. These tools originated in the 1970s, when the change from batch to interactive programming stimulated the development of innovative languages, tools, environments, and other utilities we take for granted. Microsoft Research has developed two generations of tools, some of which Microsoft developers already use to find and correct bugs. These correctness tools can improve software development by systematically detecting programming errors.